Application of Using Internet Technology to Increase Student Learning Enthusiasm at MAS Yaspendi Sungai Iyu, Bendahara District, Aceh Tamiang Regency - Tina (Indonesian Journal of Society Development, 2022)
This dedication article aims to describe the application of the use of internet technology to increase student learning enthusiasm at MAS Yaspendi Sungai Iyu, Bendahara sub-district, Aceh Tamiang Regency. The purpose of writing this service article is as education and information for readers. This type of article is a qualitative service that seeks to describe and describe a portrait of the sincere and sincere dedication of a madrasa teacher that has been carried out at the Yaspendi Sungai iyu private aliyah madrasah and then described in a structured manner by following the applicable rules of writing scientific papers. The data collection technique in this service article is observation, namely the author is directly involved in giving himself to MAS Yaspen Sungai Iyu and interviewing several figures, namely the head of the madrasa, the head of administration, and the teachers of MAS Yaspendi Sungai Iyu, Bendahara District, Aceh Tamiang Regency. The results of the dedication show that, the application of Internet Media to MAS Yaspendi Sungai iyu, Bendahara District, Aceh Tamiang Regency, which makes visualization more interesting in learning at MAS Yaspendi Sungai iyu, Bendahara District, Aceh Tamiang Regency